Modelling of the buckling of a diaphragm–spine structure for a wave energy converter. (5th April 2017) - Collins, K.M.; Meng, M.; Le, H.R.; Greaves, D.; Bellamy, N.W.
Abstract: A wide range of wave energy converter (WEC) designs exists, and the SeaWave WEC uses an unstable buckled spine mode of operation. The SeaWave consists of a hose and buckled spine-diaphragm, which pumps air along the device under wave action. A physical model and finite element analysis (FEA) is compared to a previous theoretical model in this paper. The FE model was developed in ABAQUS 6.14 using shell, solid and contact elements and the analysis was done with a quasi-static approach to reduce the computational costs. The physical model was a scale version of the novel arrangement of the spine and diaphragm made from steel, polycarbonate and latex rubber. Geometry of the deformed device was investigated results showed an increase in transverse and longitudinal curvature as the compression rate increased. The FEA tended to overestimate the bending stiffness of the model, and hence the transverse curvature, because certain behaviours of the physical model were not captured. The force required to switch from one buckled state to another was measured both in the physical and FEA models and the potential energy storage was estimated to be 0.5 J/m of device at a compression rate of 0.1%. Graphical abstract: Highlights: Snap-through force of 3D anisotropic layered buckled model wave energy converter can be computed with FEA Stiffer longitudinal components can result in more energy being stored in the structure (inferred from geometry) 0.5 J/m of device stored at a compression rate of 0.1%, equal to 25 kW for a full-scale device of 1m diameter, 1000 m length